(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
scientific and practical opinions were expressed on the organization of work on the philosophical education of all segments of the country’s population based on the criteria of social time during the construction of a new Uzbekistan. Also, the concepts of “social time” and “philosophical education” were socially philosophically analyzed, described and clarified taking into account the scale of the reforms taking place in my country.